Zakat dan PeranannyaA Dalam Menanggulangi Pelacuran - fadhli abdullah M; Faisol Mubarok (ITB AAS INDONESIA Surakarta, 2022)
Abstract Based on religious perspective, prostitution is evil and an act of sin. Many worries arise due to the existence of prostitution, in addition to create unrest in the community, prostitution is also worried about the spread of disease due to deviant sex. Economic underdevelopment is the dominant factor that driving prostitution. Therefore we need an instrument that can prevent and suppress prostitution itself, one of which is zakat. This study aims to determine the relationship between zakat and prostitution (PSK) and how the role of zakat in reducing the rate of prostitution. The method used in this study is a qualitative descriptive method to provide an overview of the effectiveness of zakat in preventing and suppressing the rate of prostitution. The data in this study were obtained through observations, interviews, and the author's search results on related references, both through digital and non-digital sources. The results of this study indicated that zakat is an instrument that is proven to be able to prevent and reduce the rate of prostitution through the provision of facilities and infrastructure for prostitutes, increase productivity, and increase their income.